'Mental health and self-rated health among U.S. South Asians: the role of religious group involvement'. Issue 2 (17th February 2022) - Stroope, Samuel; Kent, Blake Victor; Zhang, Ying; Spiegelman, Donna; Kandula, Namratha R.; Schachter, Anna B.; Kanaya, Alka; Shields, Alexandra E.
ABSTRACT: Objectives: Only one community-based study has assessed religious group involvement and health outcomes among South Asians in the U.S., with mixed results. Here, using a large, South Asian community-based sample, the effects of six religious group involvement predictors – religious tradition, attendance, group prayer, giving/receiving congregational emotional support, congregational neglect, and congregational criticism – were examined in relation to four health outcomes: self-rated health, positive mental health functioning, trait anxiety, and trait anger. Design: The study used a new religion/spirituality questionnaire in the Mediators of Atherosclerosis Among South Asians Living in America (MASALA), the largest study of mental and physical well-being among U.S. South Asians. Associations were assessed cross-sectionally using OLS regression in both the full sample ( N  = 928) and a subsample of congregation members ( N  = 312). Results: Jains reported better self-rated health compared to Hindus and Muslims. Group prayer involvement, when measured ordinally, was positively associated with self-rated health and mental health functioning. In reference group comparisons, individuals who participated in group prayer once/day or more had lower levels of anxiety and anger compared to several comparison groups in which individuals prayed less than once a day. Religious service attendance was associated with higher levels of anxiety. Giving/receiving congregational emotional support was positively associated with self-rated health and mental health functioning, and inversely associated with anxiety. Congregational criticism was associated with higher levels of anger and anxiety. Conclusions: This study provided a new assessment of religious group involvement and health in the U.S. South Asian population. Religious group participation was associated with mental and self-rated health in well-controlled models, indicating this is a fruitful area for further research. Group religious involvement may be a health-promoting resource for U.S. South Asians who are religiously active, but it is not an unalloyed boon.